Quizizz Gamification of Student Learning Attention and Motivation - Suwarni Suwarni; Lubna Lubna; Hasrat A Aimang; Pandu Adi Cakranegara; Dendi Pratama (STAI Hubbulwathan Duri, 2023)
Student attention and motivation are one of the factors that support student success. Therefore, teachers need to use various efforts, such as using learning media, so that learning becomes fun and students are interested in learning. This study aims to examine the effectiveness of Quizizz on students' attention and motivation. The research method used is quantitative. The population and sample in this study are grade 7.1 junior high schools in Palembang City for the 2022/2023 academic year, with a total of 31 students (one-shot case study). The data was obtained through a questionnaire, and the data analysis technique used was to determine the effectiveness with a percentage. This study concluded that the average percentage of the effectiveness of the Quizizz application on student attention was 70.1% or quite effective, while Quizizz on student learning motivation was 70.3% or quite effective. Thus, Quizizz is effective in increasing students' attention and learning motivation. If Quizizz is used by the teacher in learning, it will increase student attention and motivation.